Investigation of prescribing behavior at outpatient settings of governmental hospitals in eastern Ethiopia: an overall evaluation beyond World Health Organization core prescribing indicators - Tigist Gashaw; Mekonnen Sisay; Getnet Mengistu; Firehiwot Amare (Taylor & Francis Group, 2018)
Background Rational prescribing remains an important component of rational drug use. The World Health Organization (WHO) standardized and validated core prescribing indicators for evaluating prescribing pattern of drugs. The prescribing practice has been shown to deviate from national and WHO guidelines in Ethiopia. The aim of this study was; therefore, to investigate the overall prescribing behavior of four governmental hospitals: Hiwot Fana Specialized University Hospital (HFSUH), Federal Harar Police Hospital (FHPH), Jugel Hospital (JH) and Southeast Command III Hospital (SECIIIH), Harar, eastern Ethiopia. Methods Hospital based retrospective cross-sectional study was employed to evaluate outpatient prescriptions dispensed from January 1 - December 31, 2016. A total of 2400 prescriptions (600 from each hospital) were assessed. A combination of prescription completeness and prescribing indicator forms were used to collect the data. Result From a total of 2400 prescriptions reviewed, only HFSUH and FHPH were using standard prescription at prevalence of 92.5 and 99.8%, respectively. Name and weight of the patient were the most and the least commonly recorded information, respectively. A total of 5217 drugs were prescribed with an average number of drugs per encounter to be 2.17 (±0.39) and the highest value (2.60) was observed at FHPH. The frequency of administration was the most commonly written component (85.0%) with an average of 1.85 per prescription. Among all prescriptions analyzed, the percentage of encounters with antimicrobials and injectables prescribed were 66.9 and 26.5%, respectively. The prevalence of drugs prescribed with generic name and from essential drug list were 4644 (89.01%) and 4613 (88.42%), respectively. Among health professional related information, dispenser name was the least documented in all hospitals with the prevalence being 3.9%. Conclusion JH and SECIIIH were not using standard prescriptions at all during the review period. Besides, some important components of the prescription such as age, sex and diagnosis were not properly recorded or missed at all in the selected hospitals. The tendency of prescribing drugs with dose and dosage form was very poor. Overall, none of the core prescribing indicators was in line with the WHO standards. These and other related problems should be investigated in-depth to find out the underlying problems for which interventional strategies can be designed to reverse this worrying practice.